2016
DOI: 10.3390/agriculture6030047
|View full text |Cite
|
Sign up to set email alerts
|

Projecting Future Change in Growing Degree Days for Winter Wheat

Abstract: Southwest Oklahoma is one of the most productive regions in the Great Plains (USA) where winter wheat is produced. To assess the effect of climate change on the growing degree days (GDD) available for winter wheat production, we selected from the CMIP5 archive, two of the best performing Global Climate Models (GCMs) for the region (MIROC5 and CCSM4) to project the future change in GDD under the Representative Concentration Pathways (RCP) 8.5 and 4.5 future trajectories for greenhouse gas concentrations. Two qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Research findings indicate that a rise in the GDD index will reduce the future vegetation period, leading to shorter harvest maturity times. Various studies have revealed similar results for winter wheat in U.S. conditions (Ruiz Castillo & Gaitán Ospina, 2016), maize in Brazil conditions (Martins et al, 2019), and for cherries, apples, and wheat in Türkiye conditions (Şensoy, 2015;Turkoglu et al, 2016), as well as sunflower in the conditions of Türkiye (Gürkan, 2023;Gürkan et al, 2021). Changing climatic conditions highlight the need to adapt traditional farming practices.…”
Section: Discussionmentioning
confidence: 81%
“…Research findings indicate that a rise in the GDD index will reduce the future vegetation period, leading to shorter harvest maturity times. Various studies have revealed similar results for winter wheat in U.S. conditions (Ruiz Castillo & Gaitán Ospina, 2016), maize in Brazil conditions (Martins et al, 2019), and for cherries, apples, and wheat in Türkiye conditions (Şensoy, 2015;Turkoglu et al, 2016), as well as sunflower in the conditions of Türkiye (Gürkan, 2023;Gürkan et al, 2021). Changing climatic conditions highlight the need to adapt traditional farming practices.…”
Section: Discussionmentioning
confidence: 81%
“…In summary, the Sahel region is expected to see a higher GDD up to 287, 321, and 249°C for the future, that is, an increase by approximately 12% compared to the historical period. Previous studies by Salack et al (); Ruiz Castillo and Gaitán Ospina () found that under climate change, higher temperatures will result in a more rapid accumulation of GDD and therefore a reduction of certain crop development phases and the growth cycle. As such, the increased temperatures and CO 2 concentrations will have negative impacts on crop yields for food‐insecure regions such as West Africa.…”
Section: Resultsmentioning
confidence: 98%
“…The climatic variations play a vital role in crop development and growth but show a varying degree of relationship strength by season and location. A number of theoretical, modelling and empirical studies have already estimated the impacts of climate variability on crop yield fluctuation using different methodology and datasets at annual, seasonal and regional to national scales [39,98,100]. These studies suggested a range of climate variability impacts on crop production.…”
Section: Discussionmentioning
confidence: 99%